Stock liquidity and second blockholder as drivers of corporate value : evidence from Latin America (2015)
This paper examines the relationship between firm value and blockholders in Latin America. Econometric results for a comprehensive data set of more than 550 firms listed in the six largest stock markets of the region support a positive effect of variables measuring the existence, contestability, dispersion and identity of blockholder on performance (Tobin's Q) only for highly liquid stocks. The identity of the second largest blockholder (family, foreign, financial or the State) emerges as critical for such effects. The study supports the voice and exit approach as a disciplinary mechanism on firm performance.